Vertebral artery safe zone in anterior odontoid screw fixation - Malhotra, Rashmi; Devi, Bharti; Sharma, Urvi; Arora, Rajnish; Kandwal, Pankaj; Singla, Mukesh (International Journal of Research in Orthopaedics, 2026)
Background: Anterior odontoid screw fixation is a surgical technique for management of Type II odontoid fractures. The vertebral artery (VA) is located near odontoid process, making it more susceptible to injury during screw fixation. So, present study aimed to determine anatomical safe zone, which improves accuracy in screw fixation and enhances operative outcomes. Methods: This observational study was conducted in the Department of Anatomy at All India Institute of Medical Sciences (AIIMS), Rishikesh, Uttarakhand, India. Total of 10 formalin-fixed cadaver necks were dissected. Inter-VA distances were measured from midline C2 to left and right sides of VA loops. Each measurement was repeated independently, and CT angiographic data were also analysed for comparison with cadaveric findings. Results: Inter-VA distance in cadavers ranged from 28 mm to 36.1 mm, with a mean of 32.95±2.72 mm. The mean distance from the C2 midline to right VA loop was 15.61±1.25 mm, while left measured 17.24±1.80 mm, indicating a relatively wider zone on left side. CT angiographic measurements demonstrated narrower inter-VA distances (mean 25.3±3.29 mm), significant anatomical variability and differences between in-vivo and cadaveric assessments. Conclusions: An accurate understanding of inter VA distance at the C2 level is critical for safe anterior cervical surgical approaches. Understanding these morphometric variations enables surgeons to anticipate high-risk areas and determine the optimal screw trajectory and size. As a result, pre-operative CT Angiography examination of the VA path is critical for reducing problems and ensuring optimal surgical outcomes at C2 level.